The dinner list eaudiobook A novel. - Serle, Rebecca (Macmillan Audio, 2018)
"With delicate intimacy, author Rebecca Serle narrates a story that involves a surrealist dinner party and reflections on a decade of love and heartache...magic and emotive undertones make this audiobook bewitching." — AudioFile Magazine This program is read by the author. "We've been waiting for an hour." That's what Audrey says. She states it with a little bit of an edge, her words just bordering on cursive. That's the thing I think first. Not: Audrey Hepburn is at my birthday dinner, but Audrey Hepburn is annoyed." At one point or another, we've all been asked to name five people, living or dead, with whom we'd like to have dinner. Why do we choose the people we do? And what if that dinner was to actually happen? These are the questions Rebecca Serle contends with in her utterly captivating audiobook, The Dinner List. When Sabrina arrives at her thirtieth birthday dinner she finds at the table not just her best friend, but also three significant people from her past, and well, Audrey Hepburn. As the appetizers are served, wine poured, and dinner table conversation begins, it becomes clear that there's a reason these six people have been gathered together. Delicious but never indulgent, sweet with just the right amount of bitter, The Dinner List is a romance for our times. Bon appetit. Praise for The Dinner List: "It's Serle's unflinching investigation into the triumph and failings of love that makes this book one of a kind. A touch magic, a touch tragic, and absolutely compelling from beginning to end." — Stephanie Danler, New York Times bestselling author of Sweetbitter